2000
DOI: 10.1177/089033440001600406
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Individualized Professional Support on Duration of Breastfeeding: A Randomized Controlled Trial

Abstract: A trial was conducted with 51 women randomly assigned either to a conventional nursing care group or to an individualized professional support group to examine the effect of professional support on breastfeeding status at 4 weeks postpartum. All participants identified themselves as having no prior support. At 4 weeks postpartum, 17 out of 25 (68%) and 26 out of 26 (100%) women in the control and intervention groups, respectively, continued to breastfeed (P = .005). Results indicate that postpartum care augmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 25 publications
0
39
0
Order By: Relevance
“…Based on the results of several studies, exclusive breastfeeding increases when there is support for breastfeeding (37)(38)(39)(40)(41). Breastfeeding instructions can improve the results of breastfeeding, e.g., by help solve breastfeeding problems (42).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the results of several studies, exclusive breastfeeding increases when there is support for breastfeeding (37)(38)(39)(40)(41). Breastfeeding instructions can improve the results of breastfeeding, e.g., by help solve breastfeeding problems (42).…”
Section: Discussionmentioning
confidence: 99%
“…30 In contrast, when postpartum home and phone contact were added to a hospital-based intervention to women who intended to breast-feed, 100% of Intervention group women were breast-feeding at 4 weeks, compared to 68% in the controls. 31 Overall, continuity of care and individualized support appear to be most successful. The decision to initiate breast-feeding is generally made early, often before 24 weeks, whereas extending the duration of breast-feeding requires post-partum management.…”
Section: State Of the Artmentioning
confidence: 99%
“…Information and support form significant others and sufficient advice from health professionals has been shown to contribute to the feelings of competence and success of mothers in their new role and to be associated significantly with satisfaction with services received (Murray et al, 2000;Tarkka, 2003;Leahy Warren, 2005). A trial in Toronto, Canada, showed that postpartum care augmented with individualized professional support significantly increased the duration of breastfeeding in the first month postpartum (Porteous et al, 2000).…”
Section: Overview Of the Literaturementioning
confidence: 99%